Synthesis of Fused Heterocyclic Compounds by Using Formamide Derivatives as C1 Source in the Presence of Mukaiyama Reagent as the Catalyst - Ghonchepour, Ehsan; Islami, Mohammad R.; Nejadshafiee, Vajihe (Letters in Organic Chemistry, 2023)
An efficient one-pot synthesis of the benzimidazoles and benzothiazole has been developed from the reaction between 1,2 phenylenediamine and 2-aminothiophenol compounds via DMF and DEF as C1 source in the presence of Mukaiyama Reagent (CMPI) as a new organocatalyst. This method was designed based on the principle of green chemistry to avoid the use of any expensive and toxic transition-metal catalyst. All products were known and characterized by FT-IR, CHNS, 1H and 13C NMR data, and also were compared with their physical data with those reported in the literature.
Keywords: DMF